2020
DOI: 10.1108/ijsms-01-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Attachment points, team identification and sponsorship outcomes: evidence from the Indian Premier League

Abstract: PurposeThis paper tests and validates a conceptual model linking the attachment points, team identification, attitude towards the team sponsors and the behavioural intentions in the context of Indian Premier League (IPL), while testing for the moderating effects of age and gender.Design/methodology/approachData were collected from 1,053 participants through both online and offline survey and then analyzed using exploratory factor analysis (EFA) and structural equation modelling (SEM).FindingsAttachment points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 109 publications
(139 reference statements)
1
30
0
3
Order By: Relevance
“…Thus, it is consistent with prior research and marketing theory showing a positive relationship between attitude and purchase intention (e.g. Dos Santos et al, 2020;Fishbein and Ajzen, 1980;Kamath et al, 2020;Zhang et al, 2020), as well as with Bennett et al's (2006) argument that brand attitude possesses a positive impact on purchase intention. Furthermore, it aligns with the result of Rossiter and Percy (1991) that purchase intention influenced by music was mediated by consumers' brand attitude (requoted in Ballouli and Bennet, 2014).…”
Section: Hierarchy-of-effects Modelsupporting
confidence: 90%
“…Thus, it is consistent with prior research and marketing theory showing a positive relationship between attitude and purchase intention (e.g. Dos Santos et al, 2020;Fishbein and Ajzen, 1980;Kamath et al, 2020;Zhang et al, 2020), as well as with Bennett et al's (2006) argument that brand attitude possesses a positive impact on purchase intention. Furthermore, it aligns with the result of Rossiter and Percy (1991) that purchase intention influenced by music was mediated by consumers' brand attitude (requoted in Ballouli and Bennet, 2014).…”
Section: Hierarchy-of-effects Modelsupporting
confidence: 90%
“…Current Varsity Softball Players reported stronger attachment to NPF teams and softball players coupled with highest attendance and viewership of NPF games, followed by Former Varsity Softball Players and finally Parents segments. Similarly, Kamath et al (2021) found women to hold stronger attachment to sport teams due to their attachment to the sport. These findings point to the impact of life-stage on women's sport spectatorship as attachment and consumption declined from Current VSP to Former VSP to Parents.…”
Section: Pro Softball Fan Segmentsmentioning
confidence: 95%
“…Hallmann et al (2018) identified attachment with the team, coach and women's sport as the defining points for German and Japanese Women's National Soccer Team fans, while attachment to football was the predictor of fans' attendance intentions. Kamath et al (2021) reported gender differences in the relationship between attachment points and team identification; male and female fans reported stronger attachment to the players and sport, respectively leading into their team identification. As such, attachment is a multidimensional construct.…”
Section: Literature Reviewmentioning
confidence: 97%
“…One key attribute of the sport product is that is brings out incredible individual identification and emotional attachment. Affective results of sponsorship activities, for example, attitude, preference, inclination, psychological attachment or positive beliefs, have been explored in the sponsorship literature (Kamath et al , 2020). Attachment constitutes “a multidimensional property of material item ownership which speaks to the level of linkage perceived by a person between him/herself and a specific item” (Schultz et al , 1989, p. 360).…”
Section: Theoretical Backgroundmentioning
confidence: 99%